(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This research attempts to shed light on the issue of growing or uncontrolled population growth, especially from the point of view of Robert Maltus as one of the inhabitants who left their silence in this area. This study also addresses several key aspects: First, the reasons behind population growth such as migration, low mortality due to improved health care, attention to women’s reproductive health and availability of medication. Second: the relationship between both the population increase and the food problem, from the point of view of Maltos, who believes that there is a direct relationship between the two variables, the more the population has worsened the problem of food. Thirdly, reference is made to the main effects that unbalanced population growth may have on the environment on the one hand, such as continued logging, population expansion, the need for fresh drinking water, pollution of air, water, soil, and the inability to absorb waste. On the social side, poverty, unemployment and the low social level, . The most prominent solutions presented by Maltos to solve the population problem include ethical barriers and natural contraindications. Fifth: To review some attitudes on the population issue such as the theory of Thomas Sadler, James Stewart, Herbert Spencer, Karl Marx, and to indicate the extent of intersection or difference with the theory of Maltos.